“INSPIRED BY REAL EVENTS”—MEDIA (AND) MEMORY IN STEVEN SPIELBERG’S MUNICH (2005) (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
Steven Spielberg’s 2005 film Munich tells the story of an Israeli counter-terrorist team in the aftermath of the hijacking and massacre at the Olympic Games in 1972. The film spawned broad discussion about its historical accuracy and its political standpoint. While criticism primarily focused on the historiographical representation of the actions depicted, this paper analyzes in two steps the genuinely filmic mode of historical representation ofMunich. First, the analysis discusses the interplay of two conflicting narrative strategies that negotiate the character development with the political struggle. And second, analysis focuses on the two formal devices at the core of the narrative conflict: The reflexive framing of television in the depiction of the Munich massacre as a traumatic media event and the excessive transformation of its memory in a series of flashbacks. Such elaboration of the narrative and formal strategies reveals the implicit historiographical structures of the film and suggests that the notion of ‘cultural trauma’ serves as the preferential—but problematic—template in telling the history of terrorism and violence.